Prognostic value of interferon-γ release assays and tuberculin skin test in predicting the development of active tuberculosis (UK PREDICT TB): a prospective cohort study. Issue 10 (October 2018) - Abubakar, Ibrahim; Drobniewski, Francis; Southern, Jo; Sitch, Alice J; Jackson, Charlotte; Lipman, Marc; Deeks, Jonathan J; Griffiths, Chris; Bothamley, Graham; Lynn, William; Burgess, Helen; Mann, Bobby; et al.
Summary: Background: Tackling tuberculosis requires testing and treatment of latent tuberculosis in high-risk groups. The aim of this study was to estimate the predictive values of the tuberculin skin test (TST) and two interferon-γ release assays (IGRAs) for the development of active tuberculosis in high-risk groups—ie, people in recent contact with active tuberculosis cases and from high-burden countries. Method: In this prospective cohort study, we recruited participants from 54 centres (eg, clinics, community settings) in London, Birmingham, and Leicester in the UK. Participants were eligible if they were aged 16 years or older and at high risk for latent tuberculosis infection (ie, recent contact with someone with active tuberculosis [contacts] or a migrant who had arrived in the UK in the past 5 years from—or who frequently travelled to—a country with a high burden of tuberculosis [migrants]). Exclusion criteria included prevalent cases of tuberculosis, and participants who were treated for latent tuberculosis after a positive test result in this study. Each participant received three tests (QuantiFERON-TB Gold-In Tube, T-SPOT. TB, and a Mantoux TST). A positive TST result was reported using three thresholds: 5 mm (TST-5), 10 mm (TST-10), and greater than 5 mm in BCG-naive or 15 mm in BCG-vaccinated (TST-15) participants. Participants were followed up from recruitment to development of tuberculosis or censoring. Incident tuberculosis cases were identified by national tuberculosis databases, telephone interview, and review of medical notes. Our primary objective was to estimate the prognostic value of IGRAs compared with TST, assessed by the ratio of incidence rate ratios and predictive values for tuberculosis development. The study was registered withClinicalTrials.gov, NCT01162265, and is now complete. Findings: Between May 4, 2010, and June 1, 2015, 10 045 people were recruited, of whom 9610 were eligible for inclusion. Of this cohort, 4861 (50·6%) were contacts and 4749 (49·4%) were migrants. Participants were followed up for a median of 2·9 years (range 21 days to 5·9 years). 97 (1·0%) of 9610 participants developed active tuberculosis (77 [1·2%] of 6380 with results for all three tests). In all tests, annual incidence of tuberculosis was very low in those who tested negatively (ranging from 1·2 per 1000 person-years, 95% CI 0·6–2·0 for TST-5 to 1·9 per 1000 person-years, 95% CI 1·3–2·7, for QuantiFERON-TB Gold In-Tube). Annual incidence in participants who tested positively were highest for T-SPOT. TB (13·2 per 1000 person-years, 95% CI 9·9–17·4), TST-15 (11·1 per 1000 person-years, 8·3–14·6), and QuantiFERON-TB Gold In-Tube (10·1 per 1000 person-years, 7·4–13·4). Positive results for these tests were significantly better predictors of progression than TST-10 and TST-5 (eg, ratio of test positivity rates in those progressing to tuberculosis compared with those not progressing T-SPOT. TB vs TST-5: 1·99, 95% CI 1·68–2·34; p<0·0001). However, TST-5 identified a higher proportion of participants who progressed to active tuberculosis (64 [83%] of 77 tested) than all other tests and TST thresholds (≤75%). Interpretation: IGRA-based or BCG-stratified TST strategies appear most suited to screening for potential disease progression among high-risk groups. Further work will be needed to assess country-specific cost-effectiveness of each screening test, and in the absence of highly specific diagnostic tests, cheap non-toxic treatments need to be developed that could be given to larger groups of people at potential risk. Funding: National Institute for Health Research Health Technology Assessment Programme 08-68-01.